The psychology of art and the evolution of the conscious brain - Solso, Robert L., 1933- (Cambridge, Mass. : MIT Press, 2003)
"How did the human brain evolve so that art and an appreciation of art could develop? In The Psychology of Art and the Evolution of the Conscious Brain, Robert Solso describes how a consciousness that evolved for other purposes perceives and creates art." "Drawing on his earlier book Cognition and the Visual Arts and ten years of new findings in cognitive research (as well as new ideas in anthropology and art history), Solso shows that consciousness developed gradually, with distinct components that evolved adaptively over time. One of these components is an ability to imagine objects that are not present - an ability that allows us to create (and perceive) visual art."--Jacket.
Introduction : Art ... a tutorial -- Nativistic perception and directed perception -- Nativistic perception applied to the Raft -- Directed perception applied to the Raft -- Nude descending a staircase numbers 2 -- Rebound -- Art meets science -- 1. Art and the rise of consciousness -- Changes in science, changes in art -- Traditional ways of understanding art : psychophysical dualism -- Art and mind : a unitary view -- The evolution of art and the consciousness -- The rise of consciousness as a scientific topic -- AWAREness : the five facets of consciousness -- From nucleotides to Newton -- 2. Art and evolution -- The "new and improved" brain and technology, art, language, and culture -- Neanderthals, cro-magnons, and dogs that can't hunt -- The cognitive "big bang" -- The cognitive blueprint -- Environmental and dietary changes -- Brains and adaptation -- The evolution of the brain -- 3. Art and vision -- Visual AWAREness -- Seeing the brain and eye : the dynamic properties of vision -- The eye -- Beautiful colors -- From the eye to the brain -- The visual system and the perception of art -- 4. Art and the brain -- The evolution of the consciously AWARE brain -- The cognitive big bang and the emergence of art -- What brains do -- "Raphael's brain" -- 5. About face -- Faces are special in art -- Domain specificity and faces -- What the portrait artist's brain "sees" -- The face as a reflection of the "inner person" -- 6. Illusions : sensory, cognitive, and artistic -- Sensory illusions : truth or fiction? -- Cognitive illusions : twisting truth -- Visual illusions -- Artistic illusions -- First-order isomorphism and proto-isomorphism -- 7. Perspective : the art of illusion -- Seeing a 3D world with a 2D eye -- Principles of depth perception : where is it? -- Recumbent figures : why they are so hard to draw -- 8. Art and schemata -- Schemata -- Visual dissonance -- Canonic representations -- Representational art, abstract art -- A cognitive neuroscience theory of aesthetics.
Includes bibliographical references (pages and265-272) and index.
Keywords: Consciousness; Cognition; Brain -- Evolution; Visual perception; Art -- Psychology; Art; Evolution (Biology); Brain; Consciousness; Art; Evolution (Biology); Brain; Visual perception; Cognition